2021
DOI: 10.1017/s0261444821000252
|View full text |Cite
|
Sign up to set email alerts
|

Glossing and vocabulary learning

Abstract: This article offers a critical review of research on the use of glossing and its contribution to second language (L2) vocabulary acquisition. Discussion topics include the complexity of estimating the effectiveness of glossing relative to reading non-glossed texts, the quest for optimal implementations of glossing, issues of ecological validity, and ambiguity around the nature of vocabulary learning from glosses. The general conclusion is that, despite the substantial number of research studies on this subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…In order to promote learners’ form-meaning mappings, glossed captions can be considered. Glosses in captions can be accessed by clicking on a word in the caption in order to see its meaning such as the L1 translation (see Boers, 2021 for a review on glosses for vocabulary learning). While research on the use of glossing in audio-visual input is scarce, it has been found that glosses that provide access to an L1 translation can result in significantly more form-meaning mappings than full or keyword captioning (Hsieh, 2020; Montero Perez et al, 2018; Teng, 2020).…”
Section: Learning New Vocabulary From Watching L2 Audio-visual Input ...mentioning
confidence: 99%
“…In order to promote learners’ form-meaning mappings, glossed captions can be considered. Glosses in captions can be accessed by clicking on a word in the caption in order to see its meaning such as the L1 translation (see Boers, 2021 for a review on glosses for vocabulary learning). While research on the use of glossing in audio-visual input is scarce, it has been found that glosses that provide access to an L1 translation can result in significantly more form-meaning mappings than full or keyword captioning (Hsieh, 2020; Montero Perez et al, 2018; Teng, 2020).…”
Section: Learning New Vocabulary From Watching L2 Audio-visual Input ...mentioning
confidence: 99%
“…The absence of vocabulary was an ongoing topic in the literature EFL learning context. It was frequently given little preference in language instruction and was often left to fend for itself in texts and language courses (Boers, 2021;Çakmak & Erçetin, 2018;Khan, Mustafa, et al, 2020;Teng & Zhang, 2021). Historically, vocabulary acquisition and instruction received scant attention in language education.…”
Section: Introductionmentioning
confidence: 99%
“…However, having a lack of vocabulary items about a text will cause more serious problems than the lack of grammar knowledge because having or knowing sufficient vocabulary items about the text can help students to predict what the text means. That is why, it is very necessary for the teacher to provide the students with some vocabulary items, especially the keywords, before asking or letting the students read (Boers, 2021). This means that the more words are known by the students about the texts given, the better and easier their understanding and comprehension will be.…”
Section: Thementioning
confidence: 99%
“…Harmon & Wood (2018) say that in teaching any text, one of the responsibilities of the teacher is to teach the key vocabulary and concepts so that the students can comprehend or understand the academic language of the discipline or science they are reading. Boers (2021) explain that vocabulary discussion can be done before reading, during reading, and after reading. However, they stress that after getting the text to be used in the classroom, the teacher has to decide the vocabulary items to be taught before the students begin to read the text.…”
Section: Role For Comprehensionmentioning
confidence: 99%